Applicability and discriminative value of a semiautomatic three-dimensional spherical volume for the assessment of the apparent diffusion coefficient in suspicious breast lesions: feasibility study - Hering, Jan; Stieber, Anne (Clinical imaging, 2016)
To evaluate the feasibility and accuracy of a semiautomatic, three-dimensional volume of interest (3D sphere) for measuring the apparent diffusion coefficient (ADC) in suspicious breast lesions compared to conventional single-slice two-dimensional regions of interest (2D ROIs). This institutional-review-board-approved study included 56 participants with Breast Imaging Reporting and Data System 4/5 lesion. All received diffusion-weighted imaging magnetic resonance imaging prior to biopsy (b=0-1500 s/mm2). ADC values were measured in the lesions with both methods. Reproducibility and accuracies were compared. Area under the curve was 0.93 [95% confidence interval (CI) 0.86-0.99] for the 3D sphere and 0.91 (95% CI 0.84-0.98) for the 2D ROIs without significantly differing reproducibility (P=.45). A semiautomatic 3D sphere could reliably estimate ADC values in suspicious breast lesions without significant difference compared to conventional 2D ROIs.